2012
DOI: 10.1080/10440046.2011.620227
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity Conservation Through Farming: A Landscape Assessment in KwaZulu-Natal, South Africa

Abstract: The integration of agriculture and biodiversity has become an acknowledged solution to concurrently address the development of sustainable food production systems and the preservation of natural resources. However, there are few alternative farming systems combining agricultural commodities and ecosystem services. We examined the farm and landscape dynamics of an area in South Africa which has been isolated from mainstream agriculture during a large part of last century. We used a time series of aerial photogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(16 reference statements)
1
6
0
Order By: Relevance
“…Key informant interviews in the present study revealed that the enactment and enforcement of the National Veld and Forest Fire Act of 1998 (Government of South Africa, 1998) led to a significant reduction in the use of fire as an agent for clearing land for cultivation resulting in increases in flora and fauna diversity in the area. These findings confirm the findings by Torquebiau et al (2012) that since 1942 the MTA landscape has been experiencing an increase in woody cover.…”
Section: Discussionsupporting
confidence: 91%
“…Key informant interviews in the present study revealed that the enactment and enforcement of the National Veld and Forest Fire Act of 1998 (Government of South Africa, 1998) led to a significant reduction in the use of fire as an agent for clearing land for cultivation resulting in increases in flora and fauna diversity in the area. These findings confirm the findings by Torquebiau et al (2012) that since 1942 the MTA landscape has been experiencing an increase in woody cover.…”
Section: Discussionsupporting
confidence: 91%
“…It is indeed congruent with other findings in the area [29] indicating that existing institutions (e.g., Wildlife service; Ministry of agriculture) do not have any landscape-level actions and that the policy context poses a potential barrier to landscape-level management (e.g., inconsistencies between customary norms and public legislation). This could also be related to the complex tenure and governance system existing in the area, where several authorities coexist [23]. Alternatively, the two groups of interviewees agree on the fact that the KZN landscape can provide cultural services, an interesting finding to be correlated with strong Zulu traditions in the area.…”
Section: Discussionmentioning
confidence: 97%
“…The Mathenjwa people, who had been raising cattle extensively since their arrival in the area around the 17th century, were progressively forced to abandon subsistence nomadic pastoralism and shifting cultivation at the profit of sedentary peasant farming [23]. This change in farming practices was followed by an evolution of the landscape in the last 70 years towards an increase of wooded areas on long fallows and abandoned grazing areas.…”
Section: South African Site (Kzn)mentioning
confidence: 99%
“…Farmers are taught to be reliant on external sources for inputs which often come at high costs that are practically unaffordable to many poor farming households. In a context in which the presence of extension often pushes farmers toward conventional agriculture, it is not surprising that Torquebiau et al (2012) remarked in their findings from a study that examined the factors responsible for a well-balanced landscape in an area in KwaZulu-Natal, South Africa, that: "The absence of extension services so far has probably played an important role in maintaining the landscape in its current form. Farmers tend to copy existing practices.…”
Section: Role Of Extension In Biodiversity Conservationmentioning
confidence: 90%